American Economic Review - Guiso, Author(s) Luigi; Sapienza, Paola; Zingales, Luigi; Guiso, Luigi; Sapienza, Paola; Zingales, Luigi (American Economic Review, 2015)
JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms